2020
DOI: 10.1038/s41467-020-19705-w
|View full text |Cite
|
Sign up to set email alerts
|

FIS1 encodes a GA2-oxidase that regulates fruit firmness in tomato

Abstract: Fruit firmness is a target trait in tomato breeding because it facilitates transportation and storage. However, it is also a complex trait and uncovering the molecular genetic mechanisms controlling fruit firmness has proven challenging. Here, we report the map-based cloning and functional characterization of qFIRM SKIN 1 (qFIS1), a major quantitative trait locus that partially determines the difference in compression resistance between cultivated and wild tomato accessions. FIS1 encodes a GA2-oxidase, and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 57 publications
1
57
0
Order By: Relevance
“…Our results suggest that SlBES1, as an upstream TF that directly regulates PMEU1 and associated pectin de-methylesterification, could be a powerful target to be explored to extend shelf life without defect in other quality traits to tomato fruits (Figure S4D). A previous study suggested that CRISPR-editing of a hormone biosynthetic gene generated firmer fruit without unfavorable changes in quality (Li et al, 2020). Considering that diverse phytohormone signaling components generally play essential functions via subtle control, such as transcriptional regulation on the target genes (Jiang et al, 2019), it might be potential to achieve improved agronomical traits of crops by genome editing of core signaling components of phytohormones.…”
Section: Slbes1-mediated Direct Transcriptional Inhibition Of Pmeu1 Confers To Fruit Softeningmentioning
confidence: 99%
“…Our results suggest that SlBES1, as an upstream TF that directly regulates PMEU1 and associated pectin de-methylesterification, could be a powerful target to be explored to extend shelf life without defect in other quality traits to tomato fruits (Figure S4D). A previous study suggested that CRISPR-editing of a hormone biosynthetic gene generated firmer fruit without unfavorable changes in quality (Li et al, 2020). Considering that diverse phytohormone signaling components generally play essential functions via subtle control, such as transcriptional regulation on the target genes (Jiang et al, 2019), it might be potential to achieve improved agronomical traits of crops by genome editing of core signaling components of phytohormones.…”
Section: Slbes1-mediated Direct Transcriptional Inhibition Of Pmeu1 Confers To Fruit Softeningmentioning
confidence: 99%
“…Plant height, mainly confined by stem elongation, is not only a decisive factor that affects plant architecture but also an important agronomic trait that contributes to crop yield ( Wang and Li, 2008 ). Gibberellins (GAs) are a large family of tetracyclic diterpenoid plant hormones that play important roles in multiple plant growth and developmental progresses, including promoting seed germination, stem elongation, flowering, pollen development, as well as fruit growth and firmness ( Hedden and Sponsel, 2015 ; Li et al, 2020 ). The stem elongation function of GA contributed to the Green Revolution in which mutations in GA biosynthesis or signaling are the basis for semidwarf rice and wheat, respectively ( Peng et al, 1999 ; Sasaki et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the process of tomato domestication, particular alleles or genes linked either to environmental stress or to desirable traits may have been gained or lost from the wild ancestors 31 34 . For example, the FIS1 locus that contributes to fruit firmness was positively selected during tomato domestication 35 . On the other hand, the SlHAK20 locus, which contributes to the transport of both Na + and K + during salt stress, was lost during domestication 36 .…”
Section: Discussionmentioning
confidence: 99%